2021
DOI: 10.1002/csc2.20373
|View full text |Cite
|
Sign up to set email alerts
|

Image processing and prediction of leaf area in cereals: A comparison of artificial neural networks, an adaptive neuro‐fuzzy inference system, and regression methods

Abstract: In this study, the leaf area was estimated by different regression models and new methods of image processing by using artificial intelligence (AI) in bread (Triticum aestivum L.) and durum wheat (Triticum durum L.) and triticale (×Tritosecale Wittm. ex A. Camus) at seedling, booting, and milk development stages. Data on leaf traits in 1,000 plants of breed wheat, triticale, and durum wheat were studied. Among regression models using general data, LA = + √ , LA = + (), and LA = + (∕) models had a R 2 > 90% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The ANFIS model was the most accurate LA estimator in the study’s performance criteria. This finding is consistent with Sabouri and Sajadi’s [ 38 ] findings, who reported that the ANFIS was more accurate than ANN and regression methods for estimating the LA of wheat and triticale leaves. Comparison of the selected models derived from each genotype with the final model (achieved by pooling all genotypes data) proved that the developed models accommodated the effect of changes in leaf shape between genotypes and could be used for other genotypes of plum with considerable accuracy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ANFIS model was the most accurate LA estimator in the study’s performance criteria. This finding is consistent with Sabouri and Sajadi’s [ 38 ] findings, who reported that the ANFIS was more accurate than ANN and regression methods for estimating the LA of wheat and triticale leaves. Comparison of the selected models derived from each genotype with the final model (achieved by pooling all genotypes data) proved that the developed models accommodated the effect of changes in leaf shape between genotypes and could be used for other genotypes of plum with considerable accuracy.…”
Section: Discussionsupporting
confidence: 92%
“…Shastry and Sanjay [ 37 ] describe the fundamental concept and architecture of ANFIS, as well as some of the applications of ANFIS in agriculture. Sabouri and Sajadi [ 38 ] demonstrated the efficacy of using ANFIS and ANN modeling to predict the LA of bread wheat, durum wheat, and triticale plants using image-extracted L and W dimension values. Additionally, ANFIS was successfully used to predict LA plant species using leaf L, leaf W, plant type, and a specific coefficient defined for each plant with an R 2 = 0.997.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [64,65] utilized ANNs with architectures like 2-50-1 and 2-3-1, achieving accuracy rates of 99.99% and high correlation (>0.98) for estimating leaf area in various plant species, including wheat, triticale, durum, and sesame. Another study [66] compared methods like ANN, adaptive neurofuzzy inference system, and regression, reporting accuracy ranges of 97-99% for cereals. Additionally, the study [67] assessed basic ANN, ANFIS, and regression methods, affirming the potential of ANNs in precise leaf area estimation based on leaf characteristics.…”
Section: Leaf Area Estimation Using Ann Modelmentioning
confidence: 99%
“…As one such method, an Adaptive Neuro-Fuzzy Inference System (ANFIS) is a machine learning technique that combines the learning capabilities of artificial neural networks and fuzzy logic systems for classification and modeling [ 22 ]. It was reported that [ 23 ] ANFIS and ANN modeling can be effectively used to predict leaf area in bread wheat species, and ANFIS achieved successful leaf area prediction using specific coefficients related to leaves with an accuracy of R 2 = 0.997 [ 24 ]. A tool was developed [ 25 ] to determine leaf area using a PV panel as a sensor, a wooden enclosure to protect it from the external environment, a flashlight as a light source, and a commercial digital multimeter for voltage measurements.…”
Section: Introductionmentioning
confidence: 99%